THE RELATIONSHIP BETWEEN OXYGEN UPTAKE AND WORK RATE BELOW AND ABOVE LACTATE THRESHOLD. Issue 17 (24th October 2013) - Muniz-Pumares, D; Godfrey, R; Pedlar, C; Glaister, M
Abstract : A projection of submaximal measures of work-rate (WR) and oxygen uptake ( ), assuming a linear relationship, is typically used to predict supramaximal intensities (> ) as required to determine anaerobic capacity by maximal accumulated oxygen deficit. The aims of this study were: a) to investigate whether submaximal measures of WR and displayed a linear relationship during familiar and unfamiliar exercise below and above lactate threshold (LT); and b) to determine the reliability of predicted supramaximal WRs. Eight male cyclists (mean±SD age: 41±8 years, mass: 75.6±7.6 kg, height: 1.77±0.05 m; : 4.1±0.4 L·min −1 ) completed two identical cycling trials and a running trial. In each trial, 10×3 min incremental bouts of submaximal exercise were used to determine lines-of-best-fit for the WR- relationship for: 1) the entire test; 2) values below and above LT; and 3) rolling clusters of four consecutive values. Reliability of supramaximal cycling WR (110% ) was assessed using intraclass correlation coefficient (ICC) and coefficient of variation (CV). For the entire cycling trials, slopes (10.88±1.66 ml O2 ·W −1 and 12.56±1.39 ml O2 ·W −1 ), and correlation coefficients (0.99±0.02 and 0.98±0.04) were not different. The y-intercept was greater ( p =0.041) in the first cycling trial (765±230 ml O2 ) compared with the second (494±258 ml O2 ). Slope, intercept and correlation coefficients were not different below vs. above LT and between rolling clusters of values in any trial. The CV of the predicted supramaximal WR at 110% from each cycling trial (325±40 W and 322±43 W) was 7.0%, with ICC being 0.61. These data show that WR and display a linear relationship regardless of exercise intensity or familiarity. In conclusion, linear projection of submaximal WR- measures can be used to predict supramaximal intensities as required to determine maximal accumulated oxygen deficit.